2019
DOI: 10.1186/s12902-019-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 99mTc-DTPA SPECT/CT in diagnosing Orbitopathy in graves’ disease

Abstract: BackgroundThe most frequently used methods of assessing Graves’ orbithopathy (GO) include: Clinical Activity Score (CAS), ultrasonography (USG), computed tomography (CT), and magnetic resonance imaging (MRI). There exists another, slightly forgotten, imaging method: single-photon emission computed tomography (SPECT) with the use of diethylenetriaminepentaacetic acid tagged with 99mTc (99mTc-DTPA). These days it is possible to conduct a SPECT examination fused with a CT scan (SPECT/CT), which increases the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…Orbital CT can provide information on exophthalmos and fat and muscle enlargement, which can be useful for diagnosis. The current study showed that the thickness of four EOMs in the active GO group were greater than those in the inactive GO group and control group, consistent with previous studies ( 13 , 14 ). Additionally, we found that abdominal enlargement of the EOMs, especially the inferior and medial rectus muscles, was most common in GO.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Orbital CT can provide information on exophthalmos and fat and muscle enlargement, which can be useful for diagnosis. The current study showed that the thickness of four EOMs in the active GO group were greater than those in the inactive GO group and control group, consistent with previous studies ( 13 , 14 ). Additionally, we found that abdominal enlargement of the EOMs, especially the inferior and medial rectus muscles, was most common in GO.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our study aimed to evaluate the EOMs of GO using a hybrid SPECT/CT method. SPECT/CT depiction of EOM inflammation may help clinicians to accurately evaluate the inflammatory staging of GO ( 10 , 13 ). Our findings showed that the UR of EOM, especially the medial and inferior rectus muscles, in the active GO group was higher than that in the inactive GO group and the control group, suggesting that the UR has a potential for the evaluation of inflammatory infiltration within EOMs.…”
Section: Discussionmentioning
confidence: 99%
“…SPECT/CT 0.89. MRI was found to be 0.78 and CAS 0.56 [13]. Evaluation by CAS in patients with long-term GO is not always consistent with retro-orbital activity.…”
Section: Discussionmentioning
confidence: 86%
“…SPECT+MRI, SPECT/CT, MRI and clinical activity score (CAS) were compared in a study investigating the specifics of diagnostic methods. The specificities of the diagnostic methods were found to be 0.93, 0.89, 0.78, and 0.56, respectively [13] . Evaluation by CAS in patients with long-term GO is not always consistent with retro-orbital activity.…”
Section: Discussionmentioning
confidence: 93%